DEVELOPMENT OF LOBSTER TRAPS- PRELIMINARY EXPERIMENTS WITH THREE NEW DESIGNS OF RECTANGULAR ,AUSTRALIAN POT AND INK-WELL TRANS - RAJAN, K. V MOHAN; MEENAKUMARI, B (Fishery Technology, 2017)
Result of experimentlllob&ter fishing with three new designs, namely rectmgular, Australian pot and ink-well traps at Muttam, KadiapLtnam, Colachal, Enayam and Vizhinjam, south-we&t coa&t of India during 1979-80 are reported. Preliminary studies show that Australian pot and rectmgular traps as more efficient tJ the ink-well type.